Dyslipidemia in End Stage Renal Disease: A Study on Dialysis Patients in Bangabandhu Sheikh Mujib Medical University Bangladesh - Feroz, Salahuddin; Hossain, Shah Md Zakir; Islam, Rafi Nazrul; Kaiser, Amir Mohammad; Mozaffor, Miliva; Rahman, Md Mustafizur; Selim, Md Shahidul Islam (KYAMC Journal, 2020)
Background: Dyslipidemia contributes to the high cardiovascular risk in end stage renal disease (ESRD) or in dialysis patients; however, it remains an underestimated problem. Objective: To see the extent of dyslipidemia in patients of end stage renal disease i.e. chronic kidney disease (CKD) stage 5 who underwent hemodialysis or peritoneal dialysis procedure. Materials and Methods: This cross-sectional study was conducted from September 2016 to March 2018 Bangabandhu Sheikh Mujib Medical University (BSMMU) on 55 CKD (stage 5) patients where 31 in hemodialysis (HD) (group A) and 24 in continuous ambulatory peritoneal dialysis (CAPD) (group B). Serum lipid profile was estimated in both groups by using the standard laboratory technique. Results: Dialysis adequacy (Kt/V) was found 1.46 for HD patients (group A) and 1.81 for CAPD patients (group B).All serum lipids were higher in amount in CAPD patients than HD patients-total cholesterol (222.3±24.2 mg/dl vs. 198.9±28.4 mg/dl; p<0.05), triglycerides (179.6±24.7 mg/dl vs. 176.6±24.4 mg/dl; p<0.05), HDL cholesterol (40.8±3.90 mg/dl vs. 38.5±4.95 mg/dl; p>0.05) and LDL cholesterol (145.5±22.1 mg/dl vs. 123.2±26.5 mg/dl; p<0.05). Besides, dyslipidemia was more evident in CAPD patients than HD patients, as per raised serum total cholesterol (83.33% vs. 70.97%), raised triglycerides (95.83% vs. 83.87%), raised LDL (100% vs. 77.42%) and lowering of HDL cholesterol (87.5% vs. 80.65%) were found more in group B in comparison to group A. Conclusion: Dyslipidemic risk factors are highly evident in dialysis patients and the extent of dyslipidemia is observed more in CAPD than HD patients. KYAMC Journal Vol. 11, No.-3, October 2020, Page 113-117